Case study: using video analysis of matches to track player performance and inform training - Glynn, J. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
This case study describes how video analysis of matches was used to track player performance and inform training. Over a two week training camp, two-highly trained junior players competed four times in a `best of 5 sets match` against a player of similar age and playing ability. For Player 1 selected key performance indicators (KPIs) per set of total unforced errors and service return errors were video tagged and noted. For Player 2 KPIs of total unforced errors and footwork errors were video tagged and noted. Following each match the tagged video was uploaded to dartfishtvTM to be reviewed by the player, coach and analyst. The coach highlighted high error-counts for both players in each KPI after Match 1 and was concerned to see the counts increase by + 14-90% after Match 2. Post-review, the coach decided to modify training drills with more focus on match situations with players starting every drill with a serve or return. With the exception of total unforced errors (+24%) for Player 2 in Match 3, all KPI counts were reduced from Match 2 to Match 3 (- 32-40%) and reduced further to the minimum values in Match 4 (- 23-72%). The simple but effective use of video analysis can help an experienced coach to track player performance by identifying key indicators for a player`s style of play. By applying this approach systematically a coach can use the information to modify training accordingly thereby closing the loop of: training - match - analysis - training.